Izzivi vzpostavitve podpornega e-okolja deležnikov za celovito ureditev delovnega in bivalnega okolja na primeru podjetja Aparati d.o.o. - Marič, Miha; Leskovar, Robert (2023)
The Challenges of Establishing a Supportive E-environment of Stakeholders for the Comprehensive Arrangement of the Working and Living Environment on the Example of the Company Aparati d.o.o.. The monograph consists of seven chapters, which the authors prepared in connection with the content of the project "Establishment of a supportive e-environment of stakeholders for comprehensive regulation of the working and living environment in the time of Covid-19". All chapters in the monograph, regardless of the area under consideration, have in common that the research was carried out in the company Aparati, d. o. o. Throughout the chapters, the authors follow a scholarly approach through critical reviews of relevant secondary literature sources, status review and research, discussion of findings and suggestions for improvement.
Keywords: organization; human resource management; management; digitization of business; internal regulation; legal aspects of business